2012
DOI: 10.5433/1679-0359.2012v33n3p1059
|View full text |Cite
|
Sign up to set email alerts
|

Iogurte probiótico com frutanos tipo inulina de diferentes graus de polimerização: características físico-químicas e microbiológicas e estabilidade ao armazenamento

Abstract: ResumoInvestigou-se o efeito da adição de frutanos tipo inulina de diferentes graus de polimerização (DP) nas características físico-químicas e microbiológicas e na estabilidade ao armazenamento (4 o C por 28 dias) de iogurtes probióticos desnatados. Os iogurtes foram preparados usando cultura lática tradicional (Streptococcus thermophilus e Lactobacillus delbrueckii ssp. bulgaricus) e Lactobacillus paracasei ssp. paracasei como probiótico. As formulações continham frutanos tipo inulina de DP: baixo (oligofrut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
2
1
3
Order By: Relevance
“…Titratable acidity results presented lower values when compared to those found by Pimentel et al (2012), with values between 1.11 and 1.17 g lactic acid/100 g. However, the results obtained are in accordance with the current legislation, which recommends values between 0.6 and 1.5 g lactic acid/100 g. The viable lactic bacteria had no minimum value according to the legislation, which recommends a minimum of 10 7 CFU/mL. Therefore, lyophilization preserved the physicochemical characteristics of yogurts but did not preserve the viability of viable lactic bacteria.…”
Section: Parametercontrasting
confidence: 37%
“…Titratable acidity results presented lower values when compared to those found by Pimentel et al (2012), with values between 1.11 and 1.17 g lactic acid/100 g. However, the results obtained are in accordance with the current legislation, which recommends values between 0.6 and 1.5 g lactic acid/100 g. The viable lactic bacteria had no minimum value according to the legislation, which recommends a minimum of 10 7 CFU/mL. Therefore, lyophilization preserved the physicochemical characteristics of yogurts but did not preserve the viability of viable lactic bacteria.…”
Section: Parametercontrasting
confidence: 37%
“…In the present study, the addition of the prebiotics oligofructose (PO) and inulin (PI) to dairy beverages did not affect the viability of L. paracasei, as significant differences (p> 0.05) were observed in these populations between formulations containing prebiotics (PI and PO) and the P formulation with L. paracasei only for all storage periods (Figure 2). Similarly, Pimentel, Garcia andPrudencio (2012a, 2012b) observed that the addition of inulin in yogurt containing L. paracasei did not influence these populations, which remained above 10 7 CFU / ml during refrigerated storage. Thamer and Penna (2005) studied the survival of probiotic microorganisms in fermented milk beverages and found that highly acidic products (e.g., yogurt) reduce the viability of probiotic microorganisms compared to products with low acidity (e.g., cheese), which makes it necessary to make a careful selection of strains to be used in each type of product.…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…(40) mostraram que em iogurtes armazenados sob refrigeração a acidez titulável pode apresentar alterações em maior ou menor grau, dependendo do valor inicial dela, da temperatura de refrigeração, do tempo de armazenamento e do poder de pós-acidificação das culturas utilizadas. O aumento da acidez titulável é diretamente proporcional à temperatura e ao tempo de armazenamento (41) .…”
Section: Resultsunclassified